Analisis Kandungan Akrilamida Dalam Pisang Goreng Yang Beredar di Kota Manado Menggunakan Kromatografi Cair Kinerja Tinggi (KCKT) - Tandi, Debora; Fatimawali, Fatimawali; Wehantouw, Frenly (PHARMACON, 2012)
Acrylamide can be formed as a consequence of heating athigh temperature (more than1200C) in food contains high of carbohydrate. Acrylamide was classified as carcinogeniccompound to human being. Junk food which mostly eaten by people is fries. The objectiveof this research is to identify acrylamide in banana fries marketed in Manado city usingHigh Performance Liquid Chromatography (HPLC). Samples were taken from 12 places,by 6 sub district Manado City. Acrylamide were analyzed by HPLC using Shim-Pack VPODS(4,6 x 250 nm) column, comparison of mobile phase acetonitrile and phospate acid11,45 mM (5:95), flow rate 1 ml/minuteand at wave lenght 210 nm. The result shows thatAcrylamide contains in banana fries with retention time Â±4,284 minutes. Acrylamidecontained in banana fries which marketed in Manado City were 39,65 â€“ 1789,52 Î¼g/kg.Acrylamide level in banana fries is at under lethal dose (LD50)Keywords : Acrylamide, banana fries, HPLC, Manado